2019
DOI: 10.33019/akuatik.v13i2.1474
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Keanekaragaman Jenis Ikan Berdasarkan Musim Di Sungai Penyerang Kecamatan Puding Besar Kabupaten Bangka

Abstract: Sungai Penyerang merupakan salah satu sungai yang berada di Desa Kayu Besi, Kabupaten Bangka. Perbedaan musim juga dapat menyebabkan perubahan kondisi lingkungan di ekosistem Sungai sehingga berdampak langsung pada penurunan keanekaragaman jenis ikan dan komposisi jenis. Penelitian ini bertujuan untuk menganalisis pengaruh musim terhadap keanekaragaman jenis ikan yang terdapat di Perairan Sungai Penyerang. Penelitian dilaksanakan pada bulan Januari–Maret 2018. Penelitian ini dilaksanakan di 6 stasiun pengamata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…This is in line with the survey by Santoso & Wahyudewantoro (2019), where Bagridae and Siluridae families are commonly found in peat swamp areas. Sari et al (2019) also mentioned that fish from the Siluridae family are generally found in low-pH and turbid waters.…”
Section: Catch Results Based On Speciesmentioning
confidence: 99%
“…This is in line with the survey by Santoso & Wahyudewantoro (2019), where Bagridae and Siluridae families are commonly found in peat swamp areas. Sari et al (2019) also mentioned that fish from the Siluridae family are generally found in low-pH and turbid waters.…”
Section: Catch Results Based On Speciesmentioning
confidence: 99%
“…This is because not all Channidae can adapt to all environments, such as C. lucius and C. micropeltes only inhabit calm waters with a pH of 5-7 and only eat meat or [23]. The Siluridae only have 2 pairs of barbels (Maxillary barbels and mandibular barbels) and are included in the blackfish, which spend most of their life in waters that are characterized by dark brown to blackish water colors such as lakes and swamps [24].…”
Section: Fig 1 Percentage Diagram Of the 5 Largest Families Foundmentioning
confidence: 99%
“…Waters that have currents <0.1 m/s are categorized as very slow currents. Slow to moderate currents allow food particles from upstream or falling insects and leaves from trees to be held for a long time in the waters carried by currents during rainfall, a food source for fish (Sari et al, 2019).…”
Section: Figure 2 Percentage Of Catch Type In the Dry Seasonmentioning
confidence: 99%